Factors Affecting Land and Building Tax Collection of Samut Prakan Municipality - Kantha, Thanyanan; Kietjareon, Somkiet; Soonthorn, Sitthiporn (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Current land ownership is concentrated among a small number of people who do not use the land. But if land and building taxes are collected, it may help increase economic fairness, reduce economic inequality among people in society, and reduce the problem of speculation or concentration of land ownership in Thailand. Thus, the objectives of this study were to: 1) study the level of factors affecting land and buildings tax collection of Samut Prakan Municipality, 2) study the level of land and building tax collection of Samut Prakan Municipality, 3) study the factors affecting land and building tax collection of Samut Prakan Municipality and 4) to study recommendations for improving efficiency of land and building tax collection of Samut Prakan Municipality. Methodology: The sample group was 373 people who own properties or the owners of land and buildings in Samut Prakan Municipality by multi-stage sampling from community sampling and simple random sampling. The data analysis statistics were descriptive statistics and multiple regression analysis. Results: 1) the level of factors affecting land and building tax collection of Samut Prakan Municipality overall was at a high level. 2) The level of land and building tax collection of Samut Prakan Municipality overall was at a high level. 3) There were 7 factors affecting land and building tax collection of Samut Prakan Municipality: Service, Family or companion of the taxpayer, Taxpayer, Public relations, Employee, Technology, and location. They affected land and building tax collection of Samut Prakan Municipality with a statistical significance level of .05. And 4) the recommendations were Samut Prakan City Municipality should be: thorough public relations on knowledge of land and building tax collection so that the people can understand and act correctly, increase number of employees to be enough to provide services and provide convenience in tax payment through multi-channel to avoid delays.